Dating the onset of LGM ice surface lowering in the High Alps. (1st July 2016) - Wirsig, Christian; Zasadni, Jerzy; Christl, Marcus; Akçar, Naki; Ivy-Ochs, Susan
Abstract: The general chronological outline of the Last Glacial Maximum (LGM) in the Alps is well known after more than two centuries of ice age research in Europe. Current studies focus on resolving the details of the deglaciation process after the LGM. Particularly few data in this context are available from the High Alps. Here we report chronological constraints on the onset of deglaciation in two different study areas from the Western and Eastern Alps: the Mont Blanc (Italy) and Zillertal Alps (Austria). We sampled 32 bedrock and boulder surfaces from high elevation ridges beneath the glacial trimline. The oldest 10 Be exposure ages of ∼18.5 ka correspond to the initiation of lowering of the LGM ice surface. Identical ages from both study areas suggest synchronous decay of the LGM glaciers in the accumulation zones of the Western and Eastern Alps. Thus, the High Alpine ice surface lowered roughly synchronously to the downwasting of the glacier tongues in the forelands that was completed 19–18 ka. In both study areas, ages of numerous samples that are consistently 2–3 ka younger than 18.5 ka suggest the persistance of remnant ice patches at high elevations in the Lateglacial accumulation zones approximately until the Bølling-Allerød interstadial. Graphical abstract: Highlights: Determination of initial lowering of LGM ice surface in the High Alps. Trimline dating in two study sites: Mt. Blanc (Italy) and Zillertal Alps (Austria). Lowering starts simultaneously at ∼ 18.5 ka in both study sites. Synchronous with significant retreat of the piedmont lobes soon after 19 ka. Rapid decay of LGM ice cover (∼1 km/1–2 ka) in the center of the Alps.